501 Great Days out in the UK & Ireland - Project Editor Beare, Emma (London Bounty Books, 2009)
With 501 of the UK's interesting days out, this book provides things from rural retreats and medieval castles to exhilarating roller coaster rides. It shows you some of the UK's most relaxing coastal paths and some of the most fascinating museums in the UK.
Include Index and Illustration
Keywords: Great Britain -- Ireland